Adaptabilidad ecofisiológica de organismos acuáticos tropicales a cambios de salinidad - Chung, Kyung S (Universidad de Costa Rica, 2001)
Physiological response of tropical organisms to salinity changes was studied for some marine, estuarine and freshwater fishes (Astyanax bimaculatus, Petenia karussii, Cyprinodon dearborni, and Oreochromis mossambicus), marine and freshwater crustaceans (Penaeus brasiliensis, Penaeus schmitti and Macrobrachium carcinus), and marine bivalves (Perna perna, Crassostrea rhizophorae, and Arca zebra) collected from Northeast Venezuela. They were acclimated for four weeks at various salinities, and (1) placed at high salinities to determine mean lethal salinity, (2) tested by increasing salinity 5 ‰ per day to define upper lethal salinity tolerance limit, or (3) observed in a saline gradient tank to determine salinity preference. Acclimation level was the most significant factor. This phenomenon is important for tropical aquatic organisms in shallow waters, where they can adapt to high salinity during the dry season and cannot lose their acclimation level at low salinity during abrupt rain. For saline adaptation of tropical organisms, this behavior will contribute to their proliferation and distribution in fluctuating salinity environments.